Optimizing The Recovery of State Loss Assets Through an AdministrativeCompensation Mechanism - Supriyonohadi Supriyonohadi; Lego Karjoko; Waluyo Waluyo (Asian Journal of Social and Humanities, 2026)
The settlement of losses in criminal justice proceedings may, in theory, serve as an ultimum remedium capable of delivering a sense of justice, legal certainty, and benefits to society and the state. Nevertheless, the regulatory framework in the field of state finance also provides law-enforcement instruments within the domain of public financial law, particularly an administrative compensation mechanism that can optimize the recovery of state losses alongside criminal sanctions. Based on data from the Audit Board of Indonesia (BPK) Semester II 2025 Summary of Audit Results, state losses were recorded at IDR 71.57 trillion, while the Corruption Eradication Commission (KPK) recovered only IDR 2.54 trillion over the 2020-2024 period, and the Attorney General's Office recovered IDR 24.72 billion in 2025, indicating a significant recovery gap. The research method employed was normative legal research, based on a literature review of theories and regulations in the fields of state financial law and administrative law. This study finds that the administrative compensation mechanism offers five advantages over criminal proceedings: final and binding decisions (reducing lengthy litigation), liability extended to heirs (maximizing recovery), no subsidiary custodial substitution (unlike criminal judgments), responsible parties remain productive (able to earn income for repayment), and criminal verdicts do not eliminate administrative claim authority. When properly implemented, this administrative compensation mechanism can enhance the recovery of state losses.